Evaluation of Performance Improvement of Basic Techniques of Big Ball Games as an Effort to Develop Students' Sports Talent - Okta Wahyuningsih; Faisal Ramadhan; M Rafi Handimas; Diana Widhi Rachmawati (Civiliza Publishing, Indonesia., 2026)
Physical Education, Sports, and Health (PJOK) learning has an important role in improving motor skills while supporting the identification of students' sports talents. However, the process of evaluating the basic technical skills of big ball games in schools is still often carried out subjectively and has not made optimal use of quantitative data. This study aims to evaluate the improvement of the performance of the basic technique of the big ball game as an effort to develop the sports talent of high school students. The research uses a quantitative approach with an evaluative descriptive method. The research subjects consisted of 30 high school students who participated in an eight-week learning program of the basic techniques of the big ball game. Data was collected through tests of passing, dribbling, shooting, serving, and ball control skills, and supported by observation and documentation. The results showed that the average score of students' basic engineering skills increased from 65.20 in the pretest to 82.40 in the posttest with a percentage increase of 26.38%. Improvements occurred in all aspects of the skills measured, especially in shooting ability and ball control. Further research is suggested involving larger sample numbers as well as using inferential statistical analysis to obtain stronger empirical evidence.